Considerations in Applying IEEE Recommended Practice for Protection Coordination in Industrial and Commercial Power Systems-Part I - Mardegan, Claudio Sergio; Rifaat, Rasheek (IEEE transactions on industry applications, 2016)
This paper demonstrates practical considerations when studying overcurrent protection coordination in industrial systems and applying related IEEE Standards. This paper is divided into two parts. Part one focuses on protection coordination for high-voltage and medium-voltage industrial systems. Part two covers balance of distribution system topics. The main discussed subjects are time/chronologic, current/amperometric, as well as zone selective interlocking coordination. Other factors that affect coordination are also addressed. Suitable selections of the relay time-current characteristic are presented. This paper also includes practical details for accepted coordination time interval in coordinated systems.